Methylation tolerance due to an O6-methylguanine DNA methyltransferase (MGMT) field defect in the colonic mucosa: an initiating step in the development of mismatch repair-deficient colorectal cancers. Issue 11 (14th October 2010) - Svrcek, Magali; Buhard, Olivier; Colas, Chrystelle; Coulet, Florence; Dumont, Sylvie; Massaoudi, Illiasse; Lamri, Amel; Hamelin, Richard; Cosnes, Jacques; Oliveira, Carla; Seruca, Raquel; Gaub, Marie-Pierre; et al.
Abstract : Background and aims: O 6 -Methylguanine-DNA methyltransferase (MGMT) removes methyl adducts from O 6 -guanine. Known as methylation tolerance, selection for mismatch repair (MMR)-deficient cells that are unable to initiate lethal processing of O 6 -methylguanine-induced mismatches in DNA is observed in vitro as a consequence of MGMT deficiency. It was therefore hypothesised that an MGMT field defect may constitute a preneoplastic event for the development of MMR-deficient tumours displaying microsatellite instability (MSI). Methods: MGMT expression was investigated by immunohistochemistry and the methylation status of the gene promoter by PCR in neoplastic, adjacent and distant mucosal tissues of patients with MSI or non-MSI (MSS) colorectal cancer (CRC). The cancers were familial (42 MSI, 13 MSS) or sporadic (40 MSI, 49 MSS) in origin, or arose in the context of inflammatory bowel disease (IBD; 13 MSI, 36 MSS). Colonic mucosa from patients with diverticulitis (n=20) or IBD (n=39 in 27 patients) without cancer served as controls. Results: Loss of MGMT expression was more frequent in MSI than MSS CRC (p=0.047). In comparison with MSS tumours, MSI CRC occurred more frequently adjacent to patches of mucosa that lacked MGMT expression (p=0.002). Overall, loss of MGMT expression was associated with MGMT gene promoter methylation (p=0.03). Conclusion: MGMT field defects are more frequently associated with MSI than MSS CRC. These findings indicate that methylation tolerance may be a crucial initiating step prior to MMR deficiency in the development of MSI CRC in familial, sporadic and IBD settings.